The Effect of Temperature and Aprotinin During Cardiopulmonary Bypass on Three Different Methods of Activated Clotting Time Measurement - Machin, David (J Extra Corpor Technol, 2005)
The activated clotting time (ACT) is used frequently for monitoring blood anticoagulant response with heparin before, during, and after cardiopulmonary bypass (CPB). Many cardiac procedures involving CPB require reduction of the patient’s blood temperature and use of the serine protease inhibitor, aprotinin. Three different methods of ACT measurement were compared to show the effects of different CPB temperatures and the presence of aprotinin. A total of 42 patients were included in the study: 14 received CPB at 28°C, 14 received CPB at 32°C, and 14 normothermic (37°C) CPB. Within each temperature group, seven received aprotinin. The ACT in each group of patients was measured by a celite activator (C-ACT), a kaolin activator (K-ACT), and a celite, kaolin and glass activator (MAX-ACT). All three methods of ACT measurement showed significant increases (p < .05) in clotting times at hypothermic CPB compared with normothermic groups. During heparinization the C-ACT was significantly increased (p < .05) in the presence of aprotinin. Comparability between the 3 ACT measurement methods showed a very high correlation between C-ACT and K-ACT clotting times (R(2) = .8962), and slightly lower correlation between MAX-ACT and C-ACT (R(2) = .7780), and MAX-ACT and K-ACT (R(2) = .7827). All ACT measurements are affected by changes in blood temperature. The C-ACT measurement is prolonged with aprotinin, whereas the MAX-ACT and K-ACT method of measurement in the presence of aprotinin are not significantly altered. It appears that the MAX-ACT produces lower values and may necessitate additional heparin therapy for ACT target values considered safe during CPB. Further study is required from these additional findings.